Credit risk : - Kimber, Andrew (Butterworth-Heinemann, 2004)
Credit Risk: from transaction to portfolio management' provides high level, focused analysis of the nature of credit risk in investment bank portfolio management. Written by experienced international practitioners, it offers in-depth information and advice that will help all those charged with managing credit risk at the sharp end.